Implementation of the CINTA Curriculum Through Managerial Supervision to Enhance Madrasah Quality and Culture - Sopidi Sopidi; Nurlela Nurlela; Wawan Shofwani; Nani Kurniasari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the implementation of the CINTA Curriculum through managerial supervision to enhance madrasah quality and culture. The enactment of the Decree of the Minister of Religious Affairs Number 1503 of 2025 emphasizes the integration of character values into madrasah education, requiring adaptive and value-oriented management. However, empirical evidence on how managerial supervision facilitates the internalization of these values remains limited. This study aims to develop and analyze a value-based managerial supervision model to strengthen the implementation of the CINTA Curriculum. This research employed a qualitative approach with a multisite case study design. The study was conducted in several madrasahs implementing the CINTA Curriculum, involving madrasah principals, supervisors, teachers, and relevant stakeholders. Data were collected through interviews, observations, and document analysis, and were analyzed using interactive data analysis techniques. The findings reveal that systematic and reflective managerial supervision significantly enhances teacher performance, institutional effectiveness, and the internalization of CINTA values—intelligence, inclusivity, nationalism, resilience, and religiosity—within learning practices and madrasah culture. The integration of value-based supervision also promotes holistic learning and strengthens character education. In conclusion, managerial supervision functions not only as a quality assurance mechanism but also as a transformative strategy for embedding character values in educational practices. This study offers a contextual supervision model that supports curriculum policy implementation and contributes to improving madrasah governance and educational quality.